The Smart Rivers approach: Spatial quality in flood protection and floodplain restoration projects based on river DNA. (27th January 2021) - Peters, Bart; van Buuren, Michaël; van den Herik, Keesjan; Daalder, Martijn; Tempels, Barbara; Rijke, Jeroen; Pedroli, Bas
Abstract: Many river rehabilitation projects have been implemented in the past 30 years, strengthening the natural dynamics and ecology of river systems, while reconciling the functions of flood protection, navigation, sediment extraction, and cultural identity. Still, the planning and design of floodplain projects is subject to debate on how to best follow the "natural" characteristics of specific river stretches, the "DNA of the river." Unlike many other approaches of integrated river management, this approach entails a design strategy for spatial quality in river floodplain development projects at local and regional level, where the current discharge characteristics of the upstream river basin are taken as given. Starting point is the landscape ecological basis of the river, defining the characteristic (hydro‐morphological) processes and geomorphological/geological structures in each stretch of the river and floodplain area. An in‐depth characterization of these structures and processes helps design floodplains that can accommodate the various river management and development objectives. Often economically strong functions, like flood protection, can be partnered with weaker ones, such as ecosystem restoration. To safeguard spatial quality and sustainability in these integrated projects, the governance aspect is essential. Therefore the Smart Rivers approach addresses both substantial aspects (the "DNA of the River") as well as procedural and governance elements (called the "Quality Relay"). The principles of the approach are applicable to project design along regulated rivers in densely populated areas all over the world. This article is categorized under: Water and Life > Conservation, Management, and Awareness Abstract : The design of side channels in the floodplain of Gameren, along the navigation channel of the river Rhine in the Netherlands, following the local DNA of the river. Left original situation 1994, right 2003, 4 years after reconstruction in 1999. (Photo's: Rijkswaterstaat Oost‐Nederland & RWS‐Beeldbank/Joop van Houdt).